Evaluación de la eficiencia de extractos vegetales para el control de cochinillas (Dysmicoccus brevipes) en el cultivo de banano orito (Musa acuminata) en condiciones de laboratorio. - Vaca Viscarra, William Gabriel (2018)
The production of orito banana faces a number of agents that affect the organic quality of export fruit and domestic consumption, usually caused by pests throughout the year, one of the most recurrent pests is the cochineal (Dysmicoccus brevipes), which is a vector of BSV one of the main diseases and which demands higher costs of control in the crop. The present research carried out in the Molecular Microbiology Laboratory of the Department of Biotechnology of the State Technical University of Quevedo, Manuel Haz Álvarez Campus, had the general objective of evaluating the effectiveness of natural extracts in the control of cochineal (D. brevipes) under laboratory conditions. . For the realization of the evaluations a completely randomized design (DCA) plus a control was used, in the comparison of the means between treatments of the selected variables the Tukey test (p = 0.05) was applied to obtain statistical differences, for the analysis of the LD50 and TL50 was estimated using PROBIT regression. The preparation of the natural extracts was carried out according to the established treatments and by applying directly on the cochineals, the data were recorded every 24 hours after the application of the extracts for a period of 14 days. Once the evaluation time elapsed, the percentage of mortality was obtained, showing that the Neem doses reflected values between 94.5 and 97.3% of mortality, values close to the Cochibiol treatment that the one that best control of mealybugs showed. Finally, it was determined that the application of Cochibiol effectively exerts a greater control over cochineal, but implementing the use of natural extracts is just as effective adding the application of timely cultural work in the cultivation of orito banana. Keywords: neem, barbasco, Cochibiol, woodlice, DL50, TL5O